2014
DOI: 10.1242/jeb.108902
|View full text |Cite
|
Sign up to set email alerts
|

Attachment ofGalerucella nymphaeae(Coleoptera, Chrysomelidae)to surfaces with different surface energy

Abstract: Numerous studies deal with insect attachment onto surfaces with different roughness; however, little is known about insect attachment onto surfaces that have different chemistry. In the present study, we describe the attachment structures of the water-lily leaf beetle Galerucella nymphaeae and test the hypothesis that the larval and adult stages generate the strongest attachment on surfaces with contact angles that are similar to those of leaves of their host plants. The larvae bear a smooth attachment system … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
27
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 49 publications
(63 reference statements)
0
27
0
Order By: Relevance
“…In addition, the results of previous studies on this matter have been fairly heterogeneous. In a recent publication, data from the literature dealing with force measurements of different insects on surfaces with different surface energies were carefully compared [35]. No significant dependence of insect attachment forces on water CAs was shown in the five experiments recorded in the four studies compared.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, the results of previous studies on this matter have been fairly heterogeneous. In a recent publication, data from the literature dealing with force measurements of different insects on surfaces with different surface energies were carefully compared [35]. No significant dependence of insect attachment forces on water CAs was shown in the five experiments recorded in the four studies compared.…”
Section: Resultsmentioning
confidence: 99%
“…It is important to note that in all of these studies different species, developmental stages, sexes and experimental designs were used. In some of these studies, insect species that are strongly specialized to host plants whose leaf surfaces have very specific surface energies (water CA about 80°), such as the beetle Galerucella nympheae which lives on the leaf surface of the water lily, the maximum attachment force was detected at the intermediate range of water CAs, approximately corresponding to those of the plant leaves [35]. …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Consequently, a high diversity of friction and adhesion enhancing structures has evolved among insects [1–2]. Several studies showed that not only the intrinsic structure of an attachment organ determines its function, but also environmental parameters, such as the surface roughness or/and chemistry of the substrate [1,39]. Also the ambient temperature and humidity may affect the attachment ability of adhesive organs, as it was shown in the dry adhesive pads of geckoes [1013] and spiders [14].…”
Section: Introductionmentioning
confidence: 99%
“…,49,50,51,52,53,54,55,56,57,58,59,60,61,62,63,64,65,66,67,68,69,70,71,72,73,74,75,76,77,78,79,80,81,82,83,84,85,86].…”
mentioning
confidence: 99%